Fatty Acid-Induced Lipotoxicity in Pancreatic Beta-Cells During Development of Type 2 Diabetes - Oh, Yoon S.; Bae, Gong D.; Baek, Dong J.; Park, Eun-Young; Jun, Hee-Sook (Frontiers in Endocrinology, 2018)
Type 2 diabetes is caused by chronic insulin resistance and progressive decline in beta-cell function. Optimal beta-cell function and mass is essential for glucose homeostasis and beta-cell impairment leads to the development of diabetes. Elevated levels of circulating fatty acids (FAs) and disturbances in lipid metabolism regulation are associated with obesity, and they are major factors influencing the increase in the incidence of type 2 diabetes. Chronic free FA (FFA) treatment induces insulin resistance and beta-cell dysfunction; therefore, reduction of elevated plasma FFA levels might be an important therapeutic target in obesity and type 2 diabetes. Lipid signals via receptors, and intracellular mechanisms are involved in FFA-induced apoptosis. In this paper, we discuss lipid actions in beta cells, including effects on metabolic pathways and stress responses, to help further understand the molecular mechanisms of lipotoxicity-induced type 2 diabetes.